Modern Technologies in Breast Cancer Detection and Treatment - Buriboyeva Umida Kamolovna; Arslonova Nozigul Anvarovna (Journal of Science in Medicine and Life, 2024)
This article details the advantages of modern technology in the detection of breast cancer, which has a high incidence in women worldwide, the causes of the disease, the methods of treatment, and the implementation of preventive measures.